ENGLISH BORROWINGS IN COVID-19 PANDEMIC - Abdulloh Abdulloh; Sarsono Sarsono; Ikhwan Muslim (Journal of English Language and Literature (JELL), 2020)
This study describes English borrowing or loan words during COVID-19 pandemic frequently used by public and absorped by Indonesian. Some words mostly from medical and healthcare terms, but many of them are from daily, practical, social life terms. People don’t realize that they use many unfamiliar words and phrases when they communicate in Indonesian. Those words are English borrowings. The aims of the study are ; (1) to investigate some English borrowing words or phrases, (2) to describe the borrowing process from English into Indonesian. The Qualitative Decriptive Analysis Method used in analysing English borrowings . Obtains 95 English words taken then classified into the process of borrowings. 56 words from 95 words or 58,95 % already available in Kamus Besar Bahasa Indonesia (KBBI), 39 words or 41,05% is not listed in KBBI or signed with n.a or not available. In the borrowing process obtains 34 words or 35,7% as adoption , 45 words or 47,3% as adaptation , 14 words or 14,7 % as translation, and the rest is 2 words or 2,1 % as creation process. The result shows that English borrowings absorped by Indonesian through both adoption and adaptation are quite significant, total both is 83%. It means that Indonesian is quite open language to foreign languages. This fact also shows that Indonesian is a dynamic, up to date, and modern language.